Research on mathematical model of characteristic curve of surface perception by PVDF array based on Ferguson function. (10th May 2021) - Yu, Zhen; Zhang, Chen-yang; Yu, Jing-xian
The traditional 3D shape perception and reconstruction requires the use of relatively expensive 3D scanning equipment to obtain the coordinates of discrete feature points of the 3D shape. The reconstruction accuracy is determined by the scanning accuracy of the 3D scanning device, generally, the accuracy is low. In this study, based on the PVDF piezoelectric film sensing array, the 3D topographic feature point coordinate value is perceived and acquired. According to the feature point coordinate value, the feature curve fitting of the 3D shape is obtained, and the slope information of the 3D topography characteristic curve is obtained. The mathematical model of the feature surface of PVDF array surface topography based on Ferguson curve is studied to realise the surface reconstruction of 3D complex topography. Theoretical research shows that three-dimensional complex topographic reconstruction technique based on Ferguson curve for PVDF piezoelectric film array surface topography perception has the advantages of simple principle, easy implementation and high precision of shape reconstruction. It can develop intelligent structure with three-dimensional complex shape perception function.